Optimising the biopiling of weathered hydrocarbons within a risk management framework - PROMISE. - Pollard, Simon J. T.; Hough, Rupert L.; Brassington, Kirsty J.; Sinke, Anja; Crossley, Jane; Paton, Graeme I.; Semple, Kirk T.; Risdon, Graeme C.; Jackman, Simon J.; Bone, B.; Jacobsen, Christian; Lethbridge, Gordon (Cranfield University, 2005)
Thirty years of research into petroleum microbiology and bioremediation have bypassed an important observation – that many hydrocarbon contaminated sites posing potential risks to human health harbour weathered, ‘mid-distillate’ or heavy oils (Pollard, 2003). Ex-situ biopiling is an important technology for treating soils contaminated with weathered hydrocarbons. However, its performance continues to be represented by reference to reductions in the hydrocarbon ‘load’ in the soils being treated, rather than reductions in the risks posed by the hydrocarbon contamination (Owens and Bourgouin, 2003; Tien et al., 1999). The absence of ‘risk’ from the vocabulary of many operators and remediation projects reduces stakeholder (regulatory, investor, landowner, and public) confidence in remediation technologies, and subsequently limits the market potential of these technologies. Stakeholder confidence in the biopiling of weathered hydrocarbons may therefore be improved by demonstrating process optimisation within a validated risk management framework. To address these issues, a consortium led by Cranfield University’s Integrated Waste Management Centre has secured funding from the Government’s Bioremediation LINK programme. Project PROMISE (involving BP, SecondSite Regeneration Ltd., Dew Remediation Ltd., TES Bretby (Mowlem Group), technology translators PERA, and academics from Aberdeen, Cranfield and Lancaster Universities) aims to improve market confidence in biopiling by demonstrating how this treatment may be applied within a risk m